Analisis buku ajar IPA SMP kelas VIII berdasarkan pada literasi lingkungan - Siti Rahmah; Reni Puspitasari; Romahas Lubis; Festiyed Festiyed (Universitas Negeri Padang, 2019)
The purpose of this research was to analyze junior high school science textbooks based on environmental literacy content. The research analyzed the books based on the contents of aspects of environmental literacy, namely: knowledge of the environment, cognitive skills, attitudes towards the environment and behavior towards the environment. The object of this research is the junior high school science textbook. The research population was five in 5 junior high school science textbooks that were analyzed. Sampling was carried out using a two-stage sampling technique. The results of this research indicate an imbalance in the proportion of aspects of environmental literacy contained in the book. All textbooks analyzed emphasize more knowledge of the environment. From the five books analyzed, it is known that the book which has environmental circulation is book 1, which is 78 scores. And the book that has the lowest environmental literacy is the book in book 3 which is 55 scores.